Replacement drives native β‐diversity of British avifauna, while richness differences shape alien β‐diversity. (14th October 2022) - Lazarina, Maria; Sgardelis, Stefanos P.; Michailidou, Danai‐Eleni; Tsianou, Mariana; Andrikou‐Charitidou, Aristi; Touloumis, Konstantinos; Kallimanis, Athanasios S.
Abstract: Aim: We explored the range shifts of alien and native birds, the responses of alien and native β‐diversity to abiotic factors, and the effect of native diversity on alien β‐diversity in two time periods. Location: Great Britain. Time period: 1968–1972, 2007–2011. Taxa studied: Breeding birds. Methods: We estimated range shifts of alien and native species between the periods 1968–1972 and 2007–2011. Following, β‐diversity of alien and native communities was estimated by Jaccard pairwise index ( β tot ) and partitioned into richness difference and replacement component for each period. We built abiotic generalized dissimilarity models including abiotic factors for alien and native β tot and their components and a biotic model for aliens including native taxonomic and functional diversity as predictors. Results: Most alien and half native species expanded into new regions during the 40‐year period. The native species range shifts did not exhibit a clear pattern along the longitudinal or latitudinal gradient, while alien species tended to move north‐westwards. The richness difference was the dominant component of alien β‐diversity, and the replacement component contributed mostly to native β‐diversity. Alien β‐diversity responded similarly but less strongly than native β‐diversity, to the abiotic gradients. Temperature‐related variables, distance and precipitation were the most important abiotic drivers of native and alien β‐diversity. The biotic model of alien β‐diversity explained more deviance than the abiotic model. Main conclusions: Alien species expanded into new regions over the 40 years, with alien β‐diversity driven mostly by species gains. The effect of environmental filtering on alien communities was weaker compared with native communities but was slightly reinforced in the second period compared with the first period, highlighting the role of environmental change in shaping diversity patterns. Native diversity played a key role in driving alien β‐diversity, through biotic interactions or/and by reflecting climatic suitability or niche availability for aliens.